The Effect of Combined Application of Rhodochrosite Slag and Biochar on Cadmium Uptake in Rice - Jing He; Zhixi Ye; Fugui Chen; Wentao Zhou; Xin Ma; Zhiqiang Fu (Agronomy, 2025)
Cadmium (Cd) contamination in paddy soils severely threatens rice safety and human health. Currently, the high costs and technical barriers of existing Cd remediation methods limit their development, so it’s urgent to find an economical and feasible method. Herein, the synergistic effects of rhodochrosite slag and biochar on Cd immobilization in slightly acidic Cd-contaminated paddy soils have been investigated. A field experiment with four treatments—control (CK), rhodochrosite slag (R), biochar (B), and combined rhodochrosite slag + biochar (RB)—was conducted in Hunan Province, China. Results demonstrated that RB treatment significantly increased soil pH, transferred the mobile Cd to the residual fraction, and reduced Cd availability in the soil. Cd concentrations in rice roots, stems, leaves, and brown rice decreased by 26.37%, 47.20%, 31.03%, and 51.85%, respectively, under RB treatment, achieving the lowest TF and BCF values. Furthermore, RB treatment increased rice yield by 18.73%. The synergistic interaction between biochar’s adsorption capacity and rhodochrosite slag-derived competitive ions effectively transformed Cd into stable fractions, reducing bioavailability. This study proposes a novel remediation strategy that not only enhances the Cd immobilization ability of biochar but also achieves simultaneous waste valorization and soil remediation.